It's a Whole New Ball Game: The Mitchell Report, Performance Enhancing Drugs, and Professional Sports - Schrader, Brian J. (2016)
This dissertation investigates the findings of a congressional investigation into the use of performance enhancing drugs (PEDs) in Major League Baseball, known as the Mitchell Report. It analyzes the primary arguments presented in the report, the argument for integrity, role-models, and apology specifically, through the lens of governmentality and moral regulation. It argues that the report represents a distinct mode of governance that seeks to condemn PED use in a moralizing way. This mode of governance is characterized by its emergence from a variety of locations as opposed to the relatively simple use of the state and its legal apparatus. Importantly, one of those locations includes the individual subject who is urged to self-govern without the need of external threat or recourse. The dissertation also suggests that this mode of governance is inextricable linked to rhetoric and communication